Synthesis and antibacterial effects of cobalt–cellulose magnetic nanocomposites. Issue 32 (5th April 2017) - Alahmadi, N. S.; Betts, J. W.; Cheng, F.; Francesconi, M. G.; Kelly, S. M.; Kornherr, A.; Prior, T. J.; Wadhawan, J. D.
Abstract : Green synthesis is employed to prepare cobalt/cellulose nanocomposites with antibacterial and magnetic properties. The cellulose-stabilised, cubic (α-cobalt) cobalt nanoclusters are distributed evenly over the surface of the cellulose fibres. Abstract : Green synthesis is employed to prepare cobalt/cellulose nanocomposites with cubic (α-cobalt) cobalt as a main component with antibacterial and magnetic properties. An in situ reduction of aqueous solutions of cobalt ions on a model cellulose substrate surface using hydrogen gas affords spherical, cellulose-stabilised cobalt nanoclusters with magnetic properties and an average diameter of 7 nm that are distributed evenly over the surface of the cellulose fibres. These cobalt/cellulose nanocomposites exhibit good antibacterial action against opportunistic pathogens both Gram-positive ( S. aureus ) and Gram-negative ( E. coli, A. baumannii and P. aeruginosa ), with zones of inhibition up to 15 mm, thereby encouraging the deployment of these advanced materials for the treatment of wastewater or within medical dressings. This method of preparation is compared with the analogous in situ reduction of cobalt ions on a cellulose surface using sodium borohydride as reducing agent.